2017
DOI: 10.4274/jcrpe.3556
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Mutational Features of Three Chinese Children with Congenital Generalized Lipodystrophy

Abstract: Objective:To investigate the clinical and molecular features of congenital generalized lipodystrophy (CGL) in three Chinese patients with various typical manifestations.Methods:Data on clinical symptoms, results of laboratory analyses, and previous treatments in three Chinese patients were collected by a retrospective review of medical records. All coding regions and adjacent exon–intron junction regions of AGPAT2 and BSCL2 genes were amplified by polymerase chain reaction and sequenced.Results:Generalized lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…The variant of c.545_546insCCG resulted in a disruptive inframe indel at position 182 (p.Glu182delinsasparg), which may cause the misfolding of the secondary structure of the seipin protein due to the insertion of the basic amino acid arginine and could destabilize the protein structural domain. Given that this variant has only been reported in chinese patients with cGl (13,14), it is a recurrent pathogenic variant in the chinese population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variant of c.545_546insCCG resulted in a disruptive inframe indel at position 182 (p.Glu182delinsasparg), which may cause the misfolding of the secondary structure of the seipin protein due to the insertion of the basic amino acid arginine and could destabilize the protein structural domain. Given that this variant has only been reported in chinese patients with cGl (13,14), it is a recurrent pathogenic variant in the chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…The maternally inherited variant c.545_546insccG is rare in the general population (PM2) (13,14). it has been reported in trans with a pathogenic variant at least twice (PM3_Strong) and shortens the protein product (PM4) (13).…”
Section: Genetic Findingsmentioning
confidence: 99%
“…Similarly, another report found a child who was diagnosed at 9 months of age with CGL and also developed diabetes 13 years later [ 10 ]. Finally, a series of case reports published by Indumathi et al and Friguls et al, found that children with CGL2 developed diabetes at the age of 4–5 months [ 11 , 13 , 14 ]. In our case study, our neonate developed diabetes at a very early age of 12 days and is the youngest reported CGL patient with diabetes so far.…”
Section: Discussionmentioning
confidence: 99%
“…CGL2 patients often have many physical changes, mainly including acanthosis nigricans, hirsutism, muscular hypertrophy, and acromegaly [ 65 , 90 , 93 ]. Additionally, triangular facies [ 65 , 89 , 90 ], large ears [ 74 , 89 , 94 ], prognathism [ 60 ], and hernia [ 14 , 89 , 90 ] have all been reported.…”
Section: Human Diseases Caused By Mutations Of Bscl2mentioning
confidence: 99%
“…Apart from the typical features of metabolic disturbances, CGL2 patients also have a greatly increased probability of developing mild to moderate mental disability [ 58 , 60 , 61 , 79 , 95 ]. Occasionally, symptoms of motor neuron impairment such as waddling gait [ 60 ], spastic gait [ 95 ], and developmental language disorders [ 93 ] have been reported.…”
Section: Human Diseases Caused By Mutations Of Bscl2mentioning
confidence: 99%